OFR-50-88 Mineral Investigations In The Juneau Mining District, Alaska (Eagle River Area) - Joseph M. Kurtak (The National Institute for Occupational Safety and Health (NIOSH), 2011)
The Bureau of Mines conducted a four year (1985-1988) mineral assessment of the Juneau Mining District in southeast Alaska as part of its ongoing statewide mining district evaluation program. Following an extensive literature search, the Bureau investigated mines, prospects, and mineral occurrences in the area. This report describes the results of Bureau work in the Eagle River area of the Juneau gold belt; a component of the Juneau Mining District comprising 87,000 acres between the Mendenhall Glacier and Berners Bay. Gold and silver have been the only metals having significant production from the area and occur mainly in quartz stringer and fissure type veins hosted by phyllites, greenschists, greenstones, altered diorite dikes and quartz diorite gneiss. Gold also occurs in several small placer deposits. Approximately 21,100 oz of gold and nearly 9,000 oz of silver were produced over a 60 year period. Currently, the only mining activity consists of some exploration and minor placer gold production. Inferred and indicated lode gold resources having mineral development potential total approximately 796,000 tons with a weighted average grade of 0.22 oz/ton gold.